Synthesis of Some Benzimidazolyl Chalcones - Nyati, M.; Rao, N.S.; Srivastava, Y.K.; Verma, B.L. (Asian Journal of Chemistry, 2010)
Some benzimidazolyl chalcones have been synthesized by condensation of 2-acetyl benzimidazole (3) with aromatic aldehydes in presence of aqueous KOH by microwave irradiation technique.